Effect of COVID -19 Pandemic on Mental Health of Students: A Contemporary Literature Review - Gyawali, Kalpana (Education and Development, 2020)
The globally increasing trend of COVID -19 pandemic has got worldwide attention from several nations. Along with physical health, pandemic diseases have shown a tremendous negative impact on mental health in the general population throughout the world. To find out the impact of this pandemic on the mental health of students, a systematic review of different national and international literatures was carried out to complete this study. Elevated anxiety, depression, stress, and sleeping disorder were found as the major mental disorders among the students. Most of the results of reviewed studies were based on online survey. In Nepalease context studies on the impact of Covid -19 on mental health are very limited, hence the findings might be useful to explore the possible mental problems among the Nepalese students; and the result will be helpful to follow the necessary further steps to minimize the COVID-19 induced mental problems among the targeted group.